Teriparatide Treatment Following Osteoporotic Hip Fracture in a Male Patient with Multiple Sclerosis and Current Recommendations - Sibel Başaran; İlke Coşkun Benlidayı; Rengin Güzel; Tunay Sarpel (Galenos Yayinevi, 2015)
A 58-year-old male patient with a diagnosis of multiple sclerosis (MS) who had been operated due to a low-energy subtrochanteric femoral fracture was admitted in order to plan anti-osteoporotic treatment and rehabilitation at post-operative first week. Although the patient had a history of glucocorticoid use, he had never received any preventative treatment for osteoporosis. T-scores detected by Dual energy x-ray absorptiometry (DXA) method were -4.7, -4.9 and -3.3 at femoral neck, total hip and L1-L4 vertebrae, respectively. Since the patient had severe osteoporosis, teriparatide treatment was planned. Following vitamin D supplementation, teriparatide 20 mcg/day was started. After 6 months of treatment, patient improved significantly in terms of symptoms and DXA scores. T-scores of the femoral neck, total hip and L1-L4 vertebrae improved to -3.4, -3.9 and -3.0, respectively. When teriparatide therapy was continued up to 18 months, further increase in DXA values was observed (T-scores of femoral neck, total hip and L1-L4 vertebrae were -2.9, -2.4 and -2.2, respectively). No adverse event was seen during the treatment period. Following the cessation of teriparatide therapy, alendronate and cholecalciferol combination (70 mg/2800 IU) was started. Bone health and vitamin D level are affected negatively in patients with MS due to multifactorial reasons. In order to avoid serious consequences such as hip fracture, awareness about osteoporosis should be increased and preventative strategies should be tailored from the early stages of the disease